2010
DOI: 10.1158/1538-7445.am10-3300
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3300: MYC regulation of a “poor prognosis” metastatic cancer cell state

Abstract: Gene expression signatures are used clinically as prognostic tools to determine the risk of individual patients with localized breast tumors developing distant metastasis. However, we lack a clear understanding of whether these correlative biomarkers link to a common biological network that regulates metastasis. METHODS: In order to address this question, we analyzed thirteen different well-described (including two in clinical use) “poor outcome” cancer signatures in a cell line model of estrogen receptor posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…(G) NSM activity in lysates of NIH 3T3-vector (Vector) and -c-src Y527F (Src) cells measured by an assay kit from Echelon. (H) Expression of indicated genes (Affymetrix U133Plus2.0) in cells transduced with an empty retrovirus (Vector) or pBabe encoding for ERBB2 and grown in medium supplemented with 2% horse serum for 26 hr (Wolfer et al, 2010). When indicated cells transduced with empty vector were treated with 50 ng/ml EGF for 2 hr before harvesting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(G) NSM activity in lysates of NIH 3T3-vector (Vector) and -c-src Y527F (Src) cells measured by an assay kit from Echelon. (H) Expression of indicated genes (Affymetrix U133Plus2.0) in cells transduced with an empty retrovirus (Vector) or pBabe encoding for ERBB2 and grown in medium supplemented with 2% horse serum for 26 hr (Wolfer et al, 2010). When indicated cells transduced with empty vector were treated with 50 ng/ml EGF for 2 hr before harvesting.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the transformation-associated decrease in the expression of SMPD1 was not limited to the model systems used here. An analysis of a published gene expression microarray data set (Wolfer et al, 2010) revealed ERBB2-and epidermal-growth-factor-induced decrease in SMPD1 mRNA levels in MCF10A breast epithelial cells (Figure 5H), and a database search demonstrated a highly significant cancer-associated reduction in SMPD1 expression in numerous microarray studies comparing mRNA levels in tumors originating from gastrointestinal tract, liver, head and neck, kidney, pancreas, cervix, lung, brain, and lymphoid tissue with their appropriate control tissues ( Figure S2). Also SMPD3 mRNA levels were significantly reduced in gastrointestinal and lung carcinomas as well as in diffuse large B cell lymphomas ( Figure S2).…”
Section: Transformation Alters Sphingomyelin Metabolismmentioning
confidence: 99%
“…We next investigated whether EN4 affects MYC-regulated transcriptional targets in 231MFP breast cancer cells. These highly aggressive and tumorigenic triple-negative breast cancer cells are derived from MDA-MB-231 cells that have been previously shown to be driven by MYC (Horiuchi et al, 2012;Wolfer et al, 2010;Xu et al, 2010). We performed RNA sequencing (RNA-seq) on EN4-treated 231MFP cells to identify gene expression changes (Figures 4C and 4D).…”
Section: Articlementioning
confidence: 99%